Primary aldosteronism and obstructive sleep apnea: A single-center cross-sectional study of the Japanese population. Issue 11 (19th March 2021) - Nakamura, Yoshihiro; Kobayashi, Hiroki; Tanaka, Sho; Hatanaka, Yoshinari; Fuke, Yoshinobu; Fukuda, Noboru; Abe, Masanori
Abstract : Abstract: A recent report demonstrated that the prevalence of obstructive sleep apnea (OSA) is 67.6% among Caucasian and Chinese patients with primary aldosteronism (PA). Moreover, the report showed a significant association between plasma aldosterone concentration (PAC) and the severity of OSA in Caucasian patients. However, no studies have examined the prevalence of OSA with PA or the association of its severity with PAC in the Japanese population. We retrospectively evaluated the prevalence and severity of OSA in 71 newly diagnosed Japanese patients with PA. Thirty-nine (55%) of the 71 patients were diagnosed with OSA, and 69% of PA patients with OSA reported snoring. No correlation was found between the respiratory event index (REI), snoring index, and PAC and plasma renin activity (PRA). In contrast, REI correlated significantly with body mass index (BMI), which was significantly correlated with PRA. In conclusion, although the severity of OSA did not correlate with PAC and PRA, there was a high prevalence of OSA among Japanese patients with PA. Moreover, the severity of OSA was strongly affected by BMI. Thus, the examination of OSA in patients with PA and the proper management of OSA might be important for the Japanese population. Abstract : Supplemental Digital Content is available in the text